Guidelines for Judicial Conduct - (:unkn) unknown (My University, 2016)
The following Guidelines for Judicial Conduct have been made and approved by the Judiciary of Mauritius on 23 December 2002. The following Guidelines and principles are intended to establish standards of ethical conduct of judges. They are Guidelines to be applied in the light of all relevant circumstances and consistently with the requirements of judicial independence and the law.